2017
DOI: 10.1002/cbic.201700115
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Enzymatic sp2‐C‐Methylation Process: Coupling in Situ S‐Adenosyl‐l‐Methionine Formation with Methyl Transfer

Abstract: A one-pot, two-step biocatalytic platform for the regiospecfic C-methylation and C-ethylation of aromatic substrates is described. The tandem process utilises SalL (Salinospora tropica) for in situ synthesis of S-adenosyl-l-methionine (SAM), followed by alkylation of aromatic substrates by the C-methyltransferase NovO (Streptomyces spheroides). The application of this methodology is demonstrated for the regiospecific labelling of aromatic substrates by the transfer of methyl, ethyl and isotopically labelled CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 48 publications
0
40
0
2
Order By: Relevance
“…As identified in an earlier study,M TANw as added to the reaction mixture in order to degrade the SAH analogue,which inhibits NovO. [34] In almost all examples,t he 2amino-and 2-chloro-modified cofactors outperformed SAM in methylating 5-13.O ne exception was triazole 11,i nw hich no C-(m)ethylation was observed using any of the cofactors tested. %conversions determined by RP-HPLC using aratio of the peak area (254 nm) of the ClDA analogue to SAM/SAE analogue and 5'-methylthioadenosine (or analogue).…”
Section: Zuschriftenmentioning
confidence: 83%
See 3 more Smart Citations
“…As identified in an earlier study,M TANw as added to the reaction mixture in order to degrade the SAH analogue,which inhibits NovO. [34] In almost all examples,t he 2amino-and 2-chloro-modified cofactors outperformed SAM in methylating 5-13.O ne exception was triazole 11,i nw hich no C-(m)ethylation was observed using any of the cofactors tested. %conversions determined by RP-HPLC using aratio of the peak area (254 nm) of the ClDA analogue to SAM/SAE analogue and 5'-methylthioadenosine (or analogue).…”
Section: Zuschriftenmentioning
confidence: 83%
“…As identified in an earlier study,M TANw as added to the reaction mixture in order to degrade the SAH analogue,which inhibits NovO. [34] The2 -modified alkyne cofactor 4i displayed comparable conversion (5a,5 0%)t oS AM, whereas the formation of the 2-amino-6-chloro analogue (4g)i nsitu did not form 5a. ClDA/ClDAanalogue (400 mm), l-Met/l-Ethionine (2.00 mm), SalL (2.10 mm), DTT (1.00 mm)a nd BSA (1.00 mg mL À1 ), potassiumphosphate buffer (100 mm,p H6.8), 24 h, 37 8 8C.…”
Section: Angewandte Chemiementioning
confidence: 96%
See 2 more Smart Citations
“…4,30 NovO accepts a broad spectrum of donor and acceptor substrates and it was previously shown that it methylates 1 site-selectively at the desired C-8 position. 22,31 However, a matching GT for ortho Oglucosylation still had to be identified. Although glucosylation of a broad range of ( poly)phenolic acceptors by various promiscuous GTs was reported, 13,19,20,32 the selective modification of a single hydroxyl group of a polyphenolic substrate remains a particular challenge.…”
Section: Resultsmentioning
confidence: 99%